1972
DOI: 10.1007/bf01218496
|View full text |Cite
|
Sign up to set email alerts
|

Fine structure of pancreatic islets of mice infected with the M variant of the encephalomyocarditis virus

Abstract: Seventy-seven male, 12 to 16 week old CD-1 mice were injected subcutaneously with the M variant of the encephalomyoearditis (EMC) virus. Thirteen saline-injected mice served as controls. The 45 surviving virus-injected mice were sacrificed at intervals ranging from 24 h to 15 days following injection. Blood glucose values were distinctly elevated during the first 2 days and again between the seventh and fifteenth day of the experiment. Immunoassay of pancreatic tissue revealed a lowering of the mean insulin co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

1974
1974
1985
1985

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…Previous work has shown that the severity of the metabolic disease in these animals is variable and our results confirm this claim [1,3,5]. In the present investigation, we divided convalescent mice into three groups to characterize alterations in glucose tolerance and endocrine function.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Previous work has shown that the severity of the metabolic disease in these animals is variable and our results confirm this claim [1,3,5]. In the present investigation, we divided convalescent mice into three groups to characterize alterations in glucose tolerance and endocrine function.…”
Section: Discussionsupporting
confidence: 88%
“…Morphological and biochemical studies have failed to demonstrate injury to A cells during or immediately after the acute stages of infection [4][5][6]. The function of these cells, however, appears to be altered when isolated islets and monolayer cultures of islet tissue are exposed to the virus in vitro [7,8].…”
mentioning
confidence: 99%
“…In CD-a mice a moderate infiltration of mononuclear cells has been found after EMC virus injection [16,17]. The infiltrate was found only in some of the islets, mostly in the periphery and in the surrounding tissue, including the vessels [16].…”
Section: Discussionmentioning
confidence: 99%
“…Infection of mice with this virus produces a diabetes-like syndrome which resembles in many respects the juvenile-onset type diabetes (7,13,14,30,54,80). Infection of mice with this virus produces a diabetes-like syndrome which resembles in many respects the juvenile-onset type diabetes (7,13,14,30,54,80).…”
Section: Viral Infections In Animalsmentioning
confidence: 99%